KEANEKARAGAMAN JENIS VEGETASI PADA HUTAN RAWA GAMBUT SEKUNDER DAN BELUKAR RAWA DESA SUNGAI PELANG KABUPATEN KETAPANG - Hastuti, Sali; Muin, Abdurrani; Thamrin, Eddy (Universitas Tanjungpura, 2014)
Peat swamp forest has a valuable natural richness in the form of plants. This study aimed to find out the composition and dominance of species, species diversity, and stand structure in secondary peat swamp forest and thicket swamp. The vegetation analysis in secondary peat swamp forest and thicket swamp is done by using combination method. Mentibu (Daetylocladus stenostachys Oliver) is dominant in secondary peat swamp forest of tree growth level, and mempening (Quercus conocarpa OUD) is dominant in pole, sapling, and seedling of growth level (INP = 34,74%, 32,57%, 28,96%, respectively). In thicket swamp, prepat (Combretocarpus rotundatus Danser) is a dominant for the whole of growth level (INP = 261.89%, 126,12%, 98.96%, 64.99%, respectively). The diversity index of Shannon-Wienner (H’) in secondary peat swamp forest is abundant (H’ > 1) and low in thicket swamp (H’ < 1). The secondary peat swamp forest have a normal stand structure according to de Liocourt’s law. In thicket swamp, the forest had been fire, but the vegetation development now has led to a succession of normal vertical forest structure and almost reach climax. Keywords: Peat swamp forest, composition and dominance of species, species diversity and stand structure.